Factors affecting quality of life in patients undergoing hemodialysis in Semarang, Indonesia - Lusito Lusito; Kamilia Dwi Utami; Suryani Yuliyanti; Ar-Rahmah Nurmalita; Laily Rezky Amaliyah (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2025)
The quality of life in patients with chronic kidney disease (CKD) reflects how well an individual's needs are met across three physical, psychological, and social dimensions. Measuring a patient's quality of life (QoL) helps evaluate the effectiveness of CKD therapies. This study compares patients' clinical conditions categorised by their quality of life while undergoing hemodialysis therapy for chronic kidney failure. This study compares the clinical conditions of CKD patients undergoing hemodialysis based on their QoL, using a cross-sectional design involving 82 patients from Sultan Agung Islamic Hospital, Semarang. QoL was assessed with the WHOQOL-BREF questionnaire, and demographic data were collected through interviews. Clinical data was sourced from electronic medical records. Logistic regression analysis identified influencing variables on QoL. The sample was predominantly female (62.2%), with most patients over 45 years old, meeting minimum education standards (61%), and 67.1% unemployed. Most identified as Muslim and married, with 98.8% reporting strong family support. While bivariate analysis showed no significant impact of demographic or clinical variables on QoL, multivariate analysis indicated a significant relationship with haemoglobin levels. While other factors like family support and knowledge contribute to well-being, further research with larger, more varied samples is needed to better understand the quality-of-life influences for CKD patients on hemodialysis.